HISTORY OF SUGIYONO'S ICE CREAM BUSINESS IN MEDAN: A LOCAL ECONOMIC PERSPECTIVES AND BUSINESS RESILIENCE - Sitedi Buulolo; Hadiani Fitri; Muhammad Ricky Hardiyansyah (Universitas Negeri Medan, 2026)
This study aims to reconstruct the history of the development of the Sugiyono Ice Cream Factory in Medan City for the period 1983–2025 and analyze the factors of business resilience and its economic implications from a local economic perspective. The method used is a historical method with a qualitative approach through in-depth interviews, participatory observations, and documentation. The results of the study show that this business started manually with knowledge capital from the island of Java, then gradually transformed into a hybrid production system without losing the distinctive taste. Marketing strategies based on mobile sales and social proximity have proven effective in building customer loyalty in the midst of modern product competition. The main factors of business resilience for 42 years include consistency of quality, selective technology adaptation, personal relationships with consumers, and debt-free capital structure. The local economic implications are manifested in the provision of family employment, participation in community social activities, and the strengthening of an independent people's economy. The study concludes that the sustainability of small businesses does not necessarily require massive digitalization or aggressive expansion, but rather value consistency, social closeness, and wise adaptation. Key words: History, Ice Cream, Business, Resilience.